The Divine Identity of Jesus as the Reason for Israel's Unbelief in John 12:36-43 - Lett, Jonathan (2016)
This essay explores the ways in which attention to the Servant Song (Isa 52:13-53:12) evoked by Isa 53:1 can illumine a reading of John 12:36-43. Commentators have tended to abstract these quotations from their wider narrative context and to use Isa 6:10 as the lens to interpret the relationship between the texts. As a result, John's use of Christology to explain Israel's unbelief has gone unnoticed. Closer attention to the wider context of John 12 and the original setting of the Isaiah passages reveals that the citation of Isa 53:1 activates suppressed correspondences between the servant figure and Jesus at the moment when John explains Jesus's rejection. John evokes the whole Servant Song to map Jewish rejection of Jesus onto the wider history of Israel's inability to respond to God. At the same time, Isa 53 and Isa 6 force the reader to reconcile the incongruous images of Jesus as a dishonored and disfigured servant and as the holy Lord enthroned on high in his heavenly temple. Jesus's humiliating execution on the cross expresses the very essence of God's glory, which requires a reconsideration of how human notions about glory may be mere anthropological projection. Moreover, the revelation of God's glory through the humiliation and exaltation of Jesus is also the cause of obduracy. Israel simply cannot recognize their God, who is the kind of God that comes to them in the lowliness of Jesus.
Keywords: Israel (Christian theology); Jesus Christ -- Divinity; Jesus Christ -- Person & offices; KNOWABLENESS of God; PROOF of God